Research and implementation of pedestrian detection technology based on smart road - Yunpeng WANG; Quyuan LUO; Changle LI; Guoqiang MAO (物联网学报)
Aiming at the problem of single detection function,higher cost and lower detection efficiency and reliability for current pedestrian detection,which was mostly realized by vehicle mounted equipment,a pedestrian detection technology based on smart road was proposed.By deploying a large number of low-cost,highly reliable Internet of things devices on the road,real-time detection of pedestrian information in the surrounding environment was realized.Early warning information can be provided to vehicles with very low latency wireless communication technology,which can improve road safety.At present,the prototype of the pedestrian detection system has been developed,and verified by field test,the pedestrian detection system can detect pedestrians effectively.Within the detection range of 4 meters,the accuracy of single device can reach 80%,and the accuracy of multiple cross-deployed devices can reach 100%.